Development of touristic village and creative industry in improving social welfare at Wukirsari Village, Imogiri, Bantul District - Prihatin Saraswati (Tanjong Malim, 2020)
Development of touristic village and creative industry in improving social welfare at Wukirsari Village, Imogiri, Bantul District by Prihatin Saraswati